1998
DOI: 10.1046/j.1460-9568.1998.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular galanin modulates a 5‐HT1A receptor‐mediated behavioural response in the rat

Abstract: The present studies have examined whether the neuropeptide galanin can modulate brain serotoninergic (5-HT) neurotransmission in vivo and, particularly, 5-HT1A receptor-mediated transmission. For that purpose, we studied the ability of galanin (given bilaterally into the lateral ventricle, i.c.v.) to modify the impairment of passive avoidance retention induced by the selective 5-HT1A agonist 8-hydroxy-2-(di-n-propyloamino)tetralin (8-OH-DPAT) when injected prior to training. This impairment appears to be mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Electrophysiological, behavioral, and neurochemical studies have shown that galanin exerts modulatory (mainly inhibitory) effects on both the noradrenergic and serotonergic systems (Seutin et al, 1989;Sevcik et al, 1993;Pieribone et al, 1995;Xu et al, 1998c;Razani et al, 2001;Kehr et al, 2002;see Ö gren et al, 2006). Moreover, in vivo galanin can modulate 5-HT 1A preand postsynaptic receptor functions in an antagonistic manner (see Fuxe et al, 1998;Misane et al, 1998; The action of galanin is mediated via three G proteincoupled receptors, GalR1-GalR3 (see Branchek et al, 2000), which are expressed in the LC, DR, and their projection areas (Xu et al, 1998b, c;O'Donnell et al, 1999;Burazin et al, 2000;Larm et al, 2003;Hawes and Picciotto, 2004;Hawes et al, 2005;Swanson et al, 2005). Among these receptors, GalR1 and GalR3 mainly activate G i/o types of G proteins mediating inhibitory actions of galanin (Habert-Ortoli et al, 1994;Burgevin et al, 1995;Parker et al, 1995;see Branchek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological, behavioral, and neurochemical studies have shown that galanin exerts modulatory (mainly inhibitory) effects on both the noradrenergic and serotonergic systems (Seutin et al, 1989;Sevcik et al, 1993;Pieribone et al, 1995;Xu et al, 1998c;Razani et al, 2001;Kehr et al, 2002;see Ö gren et al, 2006). Moreover, in vivo galanin can modulate 5-HT 1A preand postsynaptic receptor functions in an antagonistic manner (see Fuxe et al, 1998;Misane et al, 1998; The action of galanin is mediated via three G proteincoupled receptors, GalR1-GalR3 (see Branchek et al, 2000), which are expressed in the LC, DR, and their projection areas (Xu et al, 1998b, c;O'Donnell et al, 1999;Burazin et al, 2000;Larm et al, 2003;Hawes and Picciotto, 2004;Hawes et al, 2005;Swanson et al, 2005). Among these receptors, GalR1 and GalR3 mainly activate G i/o types of G proteins mediating inhibitory actions of galanin (Habert-Ortoli et al, 1994;Burgevin et al, 1995;Parker et al, 1995;see Branchek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Gal is an inhibitory neuropeptide that is widely expressed in the central and peripheral nervous systems in vertebrates [29]. It co-exists within neurons with several small molecular classical neurotransmitters [30] and exerts strong inhibitory actions on synaptic transmission by reducing the release of neurotransmitters [31,32]. It has been previously reported that Gal shows distinct up-regulation after pathological disturbance within the nervous system, such as peripheral nerve injury [33].…”
Section: Discussionmentioning
confidence: 99%
“…The deficit in passive avoidance by systemic 8-OH-DPAT appears to be related to activation of postsynaptic 5-HT 1A receptors in the limbic forebrain, e.g. the hippocampus (Carli et al 1993;Misane et al 1998). However, the reduction in the postsynaptic 5-HT 1A receptor response after i.c.v.…”
mentioning
confidence: 93%